Back Cover: Electrodeposited Cobalt‐Phosphorous‐Derived Films as Competent Bifunctional Catalysts for Overall Water Splitting (Angew. Chem. Int. Ed. 21/2015). Issue 21 (29th April 2015) - Jiang, Nan; You, Bo; Sheng, Meili; Sun, Yujie
<x xml:space="preserve">Abstract</x> Catalysts for water splitting play a key role in the utilization of renewable energy. In their Communication on page 6251 ff., Y. Sun and co‐workers report bifunctional catalysts derived from electrodeposited cobalt–phosphorous films, which exhibit remarkable electrocatalytic performance for both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) under strongly basic conditions and can rival the performance of integrated Pt and IrO2 systems.